2018
DOI: 10.1159/000490951
|View full text |Cite
|
Sign up to set email alerts
|

The Joint ORCA-EADPH Symposium on Sugar: The Oral Health Perspective – A Commentary

Abstract: Caries is the most prevalent chronic condition worldwide and the association between high-level intake of sugars and dental decay is strong and well established. Interestingly, to combat caries, dental practitioners and public health dentists in many countries have focused mainly on the application of different kinds of fluorides and fissure sealants but not on the reduction of sugar intake. Furthermore, for many years, sugars have not been the focus of dental research activities presented at the annual confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
2
0
2
Order By: Relevance
“…A longitudinal analysis of the 1993 Pelotas Birth Cohort study revealed that the caries lifetime increase was 66 % higher in the group of children with a high frequency of sugar consumption compared with those with low consumption, regardless of the use of dental services and regular oral hygiene (28) . These results highlight the potential that effective interventions to change eating behaviours can have on children's oral health outcomes, corroborating the argument of experts (42) .…”
Section: Discussionsupporting
confidence: 77%
“…A longitudinal analysis of the 1993 Pelotas Birth Cohort study revealed that the caries lifetime increase was 66 % higher in the group of children with a high frequency of sugar consumption compared with those with low consumption, regardless of the use of dental services and regular oral hygiene (28) . These results highlight the potential that effective interventions to change eating behaviours can have on children's oral health outcomes, corroborating the argument of experts (42) .…”
Section: Discussionsupporting
confidence: 77%
“…Questions included type of food, size of meal, frequency of eating and kind of drinking per day, snacks, candies and feeding before going to sleep. A home visit and an interview with the mother's during a weekend confirm the data reported, using an approach that summarizes the information captured by the food frequency variables and analysed (22). Frequency of tooth brushing in the house and the day care was also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…überregionalen oder flächendeckenden, klinischen intraoralen Befunden (Kariesprävalenz und Karieserfahrung) abzugleichen. Denn obgleich sich der Trend einer Verbesserung der Mundgesundheit in Deutschland sehr wahrscheinlich zukünftig verstetigt [32], wird die Zahnkaries im Kindes-und Jugendalter noch immer als eine der am meisten verbreiteten chronischen Erkrankungen weltweit betrachtet [33]. Diese Erkrankung hat unbehandelt folglich auch einen negativen Einfluss auf die Lebensqualität vulnerabler Subgruppen.…”
Section: Zielgruppe -Personen Mit Einerunclassified